2019
DOI: 10.15408/akt.v12i1.12599
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Ekspansi Jaringan Kantor dan Kinerja Keuangan Terhadap Pertumbuhan Aset Bank Syariah

Abstract: This study tests Islamic banks in Indonesia for the period 2015 – May 2019 which aims to prove the influence of bank office network expansion and bank financial performance which is proxied by the ratio of CAR, BOPO, NOM and ROA to the growth of Islamic bank assets. The strategy of expanding the bank office network and achieving the performance of Islamic banks will have an impact on the growth of assets owned by the bank. This relationship analysis is basically to examine the extent of the relationship betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
1
5
1
1
Order By: Relevance
“…The results showed that the number of office networks had no effect on the growth of Islamic bank assets. The results of this study are not in line with findings (5) which prove that the addition of bank office networks has an effect on the growth of Islamic bank assets. However, the results of this study are consistent with research conducted by (2) which found that the number of office networks has no effect on the growth of Islamic commercial bank assets.…”
Section: Resultscontrasting
confidence: 96%
See 2 more Smart Citations
“…The results showed that the number of office networks had no effect on the growth of Islamic bank assets. The results of this study are not in line with findings (5) which prove that the addition of bank office networks has an effect on the growth of Islamic bank assets. However, the results of this study are consistent with research conducted by (2) which found that the number of office networks has no effect on the growth of Islamic commercial bank assets.…”
Section: Resultscontrasting
confidence: 96%
“…The results of the study (9) indicate that the number of Islamic bank office networks has an effect on the growth of Islamic bank assets. Likewise (5) proves that the addition of bank office networks has an effect on the growth of Islamic bank assets. Thus the research hypothesis is formulated: H1: The number of office networks has an effect on asset growth…”
Section: Thinking Framework and Hypothesesmentioning
confidence: 96%
See 1 more Smart Citation
“…Net operating margin is the ratio used to measure bank management's ability to manage its productive assets to generate revenue sharing. These findings are consistent with research conducted by Ihsan (2019) which states that the Net operating margin (NOM) is not significant in influencing the growth of Islamic banking. In addition, the research results of Setiawan & Hanryono (2016) also found that inflation affects profit growth.…”
Section: 3discussionsupporting
confidence: 90%
“…Several previous researchers found that the factors that influence the company's growth are return on assets; net operating margins; non-performing financing (Candera, Amir, & Artis, 2015, Supriyanto & Sari, 2019, Setyawati & Suroso, 2016; capital adequacy ratio (Setyawati &Suroso, 2016 andIhsan, 2019); financing to deposit ratio (Candera, Amir, & Artis, 2015, Supriyanto & Sari, 2019, and Safrida & Abror, 2011; and Operating Expenses Operating Income (Ihsan, 2019). In contrast to the results of the study, return on assets (Supriyanto & Sari, 2019); Non Performing Financing (Dhiba & Esya, 2019, Setiawan & Hanryono, 2016, Aisy & Mawardi, 2016and Syafrida & Abror, 2011; net operating margin (Ihsan, 2019); capital adequacy ratio (Setiawan & Hanryono, 2016, Ichsan, Amri, & Rahmatia, 2014; financing to deposit ratio (Setyawati & Suroso, 2016, Aisy & Mawardi, 2016and Setiawan & Hanryono, 2016; and Operating Expenses Operating Income (Dhiba and Esya, 2019, Ichsan, Amri, & Rahmatia, 2014, and Setiawan & Hanryono, 2016) also found that these variables had no effect on company growth. This research is different from previous studies by using inflation as a moderating variable.…”
Section: Figure 1 Growth Of Islamic Bankingmentioning
confidence: 99%